1980
DOI: 10.1111/j.1365-2265.1980.tb03425.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF FENCLOFENAC ON THYROID FUNCTION TESTS IN VIVO AND IN VITRO

Abstract: Clinically euthyroid patients on long term maintenance therapy with the non-steroidal anti-inflammatory drug fenclofenac (Flenac) show an unusual and abnormal pattern of serum thyroid function tests. In all twelve patients studied, total T4 concentrations were grossly subnormal (mean 28.4 +/- 9.9 (SD) nmol/l and total T3 levels low-normal (mean 1.4 +/- 0.3 (SD) nmol/l), whereas rT3 (mean 0.36 +/- 0.06 (SD) nmol/l) and basal TSH levels (mean 1.9 +/- 0.5 (SD) mu/l) were within their respective normal ranges. Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Since the initiation of fenclofenac treatment was reported to be associated with a suppression of thyrotrophin release, several authors have postulated that this could be a secondary effect of displacement of thyroid hormones from their serum binding sites (Humphrey et al, 1980;Kurtz et al, 1981). However, increased serum free thyroid hormones have never been observed, and there have been several reports of steady fall in both free thyroxine and triiodothyronine (Taylor et al, 1980;Ratcliffe et al, 1980;Kurtz et al, 1981). In the absence of positive proof of such an effect the possibility remained of a direct effect of the drug upon the pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the initiation of fenclofenac treatment was reported to be associated with a suppression of thyrotrophin release, several authors have postulated that this could be a secondary effect of displacement of thyroid hormones from their serum binding sites (Humphrey et al, 1980;Kurtz et al, 1981). However, increased serum free thyroid hormones have never been observed, and there have been several reports of steady fall in both free thyroxine and triiodothyronine (Taylor et al, 1980;Ratcliffe et al, 1980;Kurtz et al, 1981). In the absence of positive proof of such an effect the possibility remained of a direct effect of the drug upon the pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al In order to distinguish between the possibility of a direct drug action upon the pituitary and secondary pituitary suppression by displaced thyroid hormones, we have examined the immediate effects of fenclofenac administration, the acute effect of the drug during tonic stimulation of the pituitary with TRH and the effect of the drug upon the response to insulin-induced hypoglycaemia. As the drug has been reported to interfere with some methods of thyroid hormone assay (Ratcliffe et al, 1980), the in uitro effect of fenclofenac upon the equilibrium dialysis method for estimating free thyroid hormones was examined.…”
mentioning
confidence: 99%
“…Thyroid hormones (T4 and T3) Replacement therapy, antigoitrogenic, and anticancer Thyroid hormone analogues (DT4, 471 3′,3′,5-TRIAC, 472 etiroxate-HCI, 473 dimethyl-3 isopropyl-L-thyronine 474 Treatment for cerebrovascular diseases and migraine Dopamine antagonist (pimozide) 254 Neuroleptic α-Noradrenergic blockers 479,480 (phentolamine, thioridazine) Neuroleptic Serotonin antagonists (metergoline, 481 cyproheptadine, 482 methysergide 483 ) Antimigraine and appetite stimulators Serotonin agonist (5-hydroxytryptophan) 463 -Glucocorticoids 484,485 Antiinflammatory, antiimmunosuppressive, and anticancer; reduction of intracranial pressure Acetylsalicylic acid 164 Antiinflammatory, antipyretic, and analgesic Growth hormone 165 * Growth promoting Somatostatin 166 Antineoplastic Octreotide 486 Opiates (morphine, 487 leuenkephalin, 488 heroin 409 ) Analgesic Clofibrate 489 Hypolipidemic Fenclofenac 403,432 Nonsteroidal antiinflammatory drug Bexarotene 490 T cell lymphoma IL-6 443 Biotin 194,195 Immune modulating Interference with biotin-strepavidin complexes DT4, Dextrothyroxine; IL, interleukin; T3, triiodothyronine; T4, thyroxine; TRH, thyrotropin-releasing hormone; TRIAC, triiodothyroacetic acid;…”
Section: Decrease Serum Tsh Concentration And/or Its Response To Trhmentioning
confidence: 99%
“…In addition to aspirin and salsalate, other NSAIDs have been evaluated, the most common ones being fenclofenac and mefenamic acid, and have been found to displace thyroid hormones from serum protein-binding sites. 403 Some studies have evaluated more commonly used NSAIDs, such as ibuprofen, naproxen, diclofenac, sulindac, and indomethacin, as compared with aspirin and salsalate. 404 One study of 25 healthy subjects who were given aspirin, salsalate, meclofenamate, ibuprofen, naproxen, or indomethacin at doses that patients usually choose for acute, limited, painful conditions showed that aspirin and salsalate induced decreases in mean total and free thyroid hormone measurements with associated changes in TSH after 1 week, confirming findings of older studies; it is interesting to note that meclofenamate induced acute increases in mean total T4, T3, and free T3 levels at 2 hours after a single dose but did not affect mean levels of thyroid hormones over a period of 1 week.…”
Section: Miscellaneousmentioning
confidence: 99%
“…This may be either familial or due to diseases such as Cushing's syndrome, acromegaly and nephrotic syndrome (Kaplan, 1984). A drug-induced reduction in the binding proteins may also occur; the drugs responsible are androgens, anabolic steroids and danazol (Graham & Gambrell, 1980;Wenzel, 1981), but the commonest cause is a drug-induced inhibition of binding, most often due to fenclofenac (Ratcliffe et al, 1980), though this drug has now been withdrawn from the UK market. Other drugs which can produce the same phenomenon are diazepam, heparin, phenylbutazone, salicylates, sulphonylureas (Wenzel, 1981), halofenate and o-p' DDD (Kaplan, 1984).…”
mentioning
confidence: 99%